2022
DOI: 10.1111/cob.12567
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, lifestyle behaviours and psychological effects of the COVID‐19 lockdown: A survey of patients attending a tertiary weight loss clinic

Abstract: Summary Lockdown measures due to coronavirus‐19 disease (COVID‐19) have impacted lifestyle factors. This study aimed to explore whether health and lifestyle behaviours changed during the 2020 COVID‐19 lockdown among patients with obesity. A specifically designed online survey and the Depression Anxiety Stress Scale (DASS‐21) were administered to patients scheduled to attend a tertiary weight management service between 6 June–12 August 2020. A total of 210 participants completed the survey; mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The quarantine changed many habits, including food, fast food and processed foods, which saw an increase in consumption and, on the other hand, physical activity, as reported in several studies, was more difficult to maintain, including what was observed in this study, in which among participants, the majority of obese people do not practice physical activity. It was also possible to observe in the study by Frankli, Janet et al (26) that 61.3% of people had weight gain.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The quarantine changed many habits, including food, fast food and processed foods, which saw an increase in consumption and, on the other hand, physical activity, as reported in several studies, was more difficult to maintain, including what was observed in this study, in which among participants, the majority of obese people do not practice physical activity. It was also possible to observe in the study by Frankli, Janet et al (26) that 61.3% of people had weight gain.…”
mentioning
confidence: 84%
“…As all the changes that obesity can cause physically in the mental issue is no different, in the study by Frankli, Janet et al (26) 20.7% said they developed severe depression and 19.5% symptoms of anxiety. The quarantine changed many habits, including food, fast food and processed foods, which saw an increase in consumption and, on the other hand, physical activity, as reported in several studies, was more difficult to maintain, including what was observed in this study, in which among participants, the majority of obese people do not practice physical activity.…”
mentioning
confidence: 97%